(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article reflects the key points of the use of artificial intelligence in the development and implementation of human resources management technologies in organizations and companies of different levels. The author explores the specifics of the organization of communication in the context of digitalization and the importance of these processes for the effectiveness of management management. Personnel management in work is considered as a structured educational and professional process, which, in addition to working moments, includes training of employees and managers in new types of interaction, work in a digital environment, and determines the prospects for the development of digital intelligence participation in personnel management.